Derivado semi-sintético cumarínico 2h-1-benzopiran-2-ona, 7- preniloxi com potencial antitumoral - Cruz, Ryldene Marques Duarte da (2016)
The 2H-1-benzopyran-2-one, 7-preniloxi (UMB-07) is a coumarin derivative from a prenylation reaction in commercial umbelliferone. Published data reported that coumarin derivatives have a range of pharmacological activities such as antibacterial, antiinflammatory and antitumor activity. Specifically for the UMB- 07, the literature reports antifungal, antibacterial and antitumor activities. However, despite being a cytotoxic compound for tumor cells, there is no studies of mechanisms of action associated with this effect. This study aimed to evaluate the toxicity and antitumor activity of UMB-07. The hemolytic effect UMB-07 was evaluated by cytotoxicity assay in peripheral blood erythrocytes of mice. UMB-07 induced a small percentage of hemolysis (0.8%) at the concentration tested (2000 mg/mL), indicating a low toxicity. In vivo, the assay was performed Preclinical acute toxicity UMB-07 to evaluate behavioral effects and estimated 50% lethal dose (LD50). UMB-07 (300 or 2000 mg/kg, intraperitoneal injection - i.p.) induced depressive effects in the central and autonomic nervous systems. The LD50 was estimated at about 1000 mg / kg. Genotoxicity UMB-07 was assessed by the micronucleus test in the peripheral blood of mice. UMB-07 (300 mg/kg - i.p.) did not induce an increase in the number of micronucleated erythrocytes, suggesting low genotoxicity. The ascitic Ehrlich carcinoma model was used to evaluate the antitumor activity UMB-07 (12.5, 25 or 50 mg/kg, i.p.) after nine days of treatment. UMB-07 (50 mg/kg) showed antitumor activity by reducing the volume parameters, mass, and the total amount of tumor cells (p <0.05). In evaluating possible mechanisms involved in this effect, it was observed that UMB-07 does not interfere with the cell cycle progression. However, antiangiogenic effect was observed for this coumarin, considering the reduction of Microvessel peritumoral (p <0.05). Still, it evaluated the possible immunomodulatory effect of UMB-07 for determination of cytokines and chemokine peritoneal fluid of animals. UMB-07 (50 mg/kg) reduced levels of CCL2 chemokine, which, in turn, is associated with angiogenesis, metastasis and tumor progression. After treatment nine days with UMB-07 was observed that there was no change in kidney and liver biochemical parameters, which was confirmed by histological analysis. The altered hematological parameters (lymphocytes and segmented) remained within normal limits for the species, suggesting low clinical significance for this finding. In vitro model, we observed reduction of nitric oxide (NO) production in peritoneal macrophages stimulated by lipopolysaccharide. However, this effect was associated with a cytotoxicity of the compound on those cells. These results together suggest that UMB-07 in vivo has low toxicity and antitumor activity with a mechanism involving anti-angiogenic effects possibly associated with the reduction of CCL2 chemokine.